PHYSIOTHERAPY FOR THE DEVELOPMENT OF PSYCHOMOTRICITY IN CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) - Oliveira da Silva, Daiele (Health and Society, 2023)
Introduction: Autistic Spectrum Disorder (ASD) in children is characterized by difficulty interacting, communicating and relating to other individuals, impairing and limiting day-to-day activities and social interaction. They are classified into three degrees, being mild, moderate and severe. These symptoms can be observed during early childhood, with the diagnosis starting at three years of age. Although there is no cure for ASD, early diagnosis and rapid intervention help to reduce the possibility of chronicity, increase treatment possibilities and minimize various symptoms. Psychomotricity is one of the means of intervention in which it has been most used, as it improves the development of motor coordination, helping with sensory characteristics, language, obtaining a better quality of life for these patients. Objective: To report and describe the importance and effectiveness of physical therapy intervention in the development of psychomotricity in children with ASD for better motor performance, improving interaction and including the individual in the social environment. Method: Research carried out in March 2023, using SciELO, Google Scholar and Pubmed databases with publication languages in Portuguese, English and Spanish. 32 articles were selected for analysis of the study, the publication and posting criteria were from the last ten years and had human beings as the object of study, specifically children. Conclusion: Through the study carried out, it was observed that through the various physiotherapeutic resources in psychomotricity, there was a significant improvement in motor development and social inclusion of children with ASD.